IMPLEMNTASI SUPERVISI AKADEMIK KEPALA SEKOLAH UNTUK MENINGKATKAN DISIPLIN DAN PROFESIONALISME GURU DI MADRASAH MIFTAHUL HUDA TAYU PATI - Tri Pudji (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purpose of this study was to determine the implementation of the principal's academic supervision to improve teacher discipline and professionalism and the obstacles faced by school principals in improving the discipline and professionalism of Miftahul Huda Tayu Madrasah teachers. This study used a qualitative approach with case study design. The results in this study are: 1) The efforts of the head of the Madrasah Tsanawiyah Miftahul Huda Tayu in improving teacher discipline are 1) Coaching and checking to see discipline, 2) providing motivation, 3) giving awards. The efforts of the head of Madrasah Tsanawiyah Miftahul in improving teacher professionalism are empowering the competencies possessed by teachers, being active in the Teacher Working Group (KKG), participating in seminar training, providing guidance for supervision. 2) Implementation of principal's academic supervision to improve teacher professionalism and discipline. The planning stage includes forming a supervision team, analyzing monitoring needs, compiling a supervision schedule, compiling supervision instruments, and disseminating supervision instruments. The implementation phase of academic supervision includes class visits, seminars, group discussions, teacher meetings, self-assessment, individual meetings, class observations, class visits. 3) Principal constraints in implementing the principal's academic supervision to improve teacher professionalism and discipline at Madrasah Tsanawiyah Miftahul Huda Tayu 1) Lack of time, 2) Lack of teacher's scientific passion, 3) Worries due to Pandemic Conditions, 4) Human resources, 5) lack of teacher commitment